Localization of the binding site of tissue-type plasminogen activator to fibrin. - Ichinose, A (1986)
Functionally active A and B chains were separated from a two-chain form of recombinant tissue-type plasminogen activator after mild reduction and alkylation. The A chain was found to be responsible for the binding to lysine-Sepharose or fibrin and the B chain contained the catalytic activity of tissue-type plasminogen activator. An extensive reduction of two-chain tissue-type plasminogen activator, however, destroyed both the binding and catalytic activities. A thermolytic fragment, Fr. 1, of tissue-type plasminogen activator that contained a growth factor and two kringle segments retained its lysine binding activity. Additional thermolytic cleavages in the kringle-2 segment of Fr. 1 caused a total loss of the binding activity. These results indicated that the binding site of tissue-type plasminogen activator to fibrin was located in the kringle-2 segment.